Dissecting Hoaxes as an Important Strategy in Maintaining Information Literacy - Dinihari, Yulian; Rafli , Zainal; Boeriswati , Endry (SALEE: Study of Applied Linguistics and English Education, 2024)
The modern mass population is affected by the hoax phenomenon in the information age, which has a negative impact on productivity, information integration, and social stability. This paper aims to contribute to the public's understanding and response to hoaxes, with a focus on literary and digital literary criticism. In this case, a careful and structured qualitative descriptive is used to identify a hoax phenomenon. This approach comes from two different perspectives. While literature analysis addresses the characteristics and nature of the information in question, other approaches involve empirical methods to examine the impact of language use on readers' perceptions and responses to hoaxes. One more example is the use of an online form that requires the use of a questionnaire that is unique to each individual. The results of the survey, which had 108 responses, showed that media literacy, intensive education, and mass media consumption were all important factors in achieving this goal. The results of this research show that there are various types of fabrication that are commonly found in the computerized period, and each has its own characteristics. One research focus is on political tricks, which are often used to influence public opinion or damage the reputation of political opponents through the spread of false claims about policies or statements taken out of context. The findings of the survey indicate that the mass media's literacy rate has increased as a result of the verification of information and analysis.